Next-generation high-speed Satellite interconnect disclosing the SpaceFibre Protocol - a system perspective - Dinelli, Gianmarco; Sterpaio, Luca Dello; Marino, Antonino; Fanucci, Luca (Springer, 2021)
This book introduces the space community to the novel SpaceFibre protocol, developed under the guidance of the European Space Agency (ESA) as the forthcoming, high speed (Gbps) communication protocol for satellite on-board communication. Since SpaceFibre is expected to follow the success of its predecessor SpaceWire protocol (Mbps), the authors provide a system-level perspective for the end-user willing to adopt this latest technology for future space missions. The authors provide a complete view of the SpaceFibre protocol, together with an analysis of all the necessary hardware and software components to integrate this technology onboard a satellite.